2014
DOI: 10.1155/2014/686201
|View full text |Cite
|
Sign up to set email alerts
|

Representation Bias, Return Forecast, and Portfolio Selection in the Stock Market of China

Abstract: Representation bias means a kind of cognitive tendency, and, for investors, it can affect their behavior in the stock market. Whether the representation bias can help the return forecast and portfolio selection is an interesting problem that is less studied. In this paper, based on the representation bias theory and current markets situation in China, a new hierarchy of stock measurement system is constructed and a corresponding set of criteria is also proposed. On each criterion, we try to measure the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Representation bias is a cognitive tendency for investors to be able to influence their behavior on the stock market (Zhao & Fang, 2014). The representation bias in this case is a cognitive bias where people can relate to their analogs and can predict the future of analogs, especially in the horizontal representation bias (Zhang, 2008).…”
Section: Representation Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Representation bias is a cognitive tendency for investors to be able to influence their behavior on the stock market (Zhao & Fang, 2014). The representation bias in this case is a cognitive bias where people can relate to their analogs and can predict the future of analogs, especially in the horizontal representation bias (Zhang, 2008).…”
Section: Representation Biasmentioning
confidence: 99%
“…The representation bias in this case is a cognitive bias where people can relate to their analogs and can predict the future of analogs, especially in the horizontal representation bias (Zhang, 2008). In the literature on financial behavior, this bias has an impact on the quality of investment (Zhao & Fang, 2014). Investors often position past returns as a representation of the potential for future returns, therefore it is found that there is a trend of the future in terms of returns (Bondt, 1998).…”
Section: Representation Biasmentioning
confidence: 99%
“…There are many studies in the literature that use the portfolio selection process and the fuzzy logic approach [2][3][4][5][6]. Xu et al proposed a new fuzzy model for portfolio selection problem.…”
Section: Introductionmentioning
confidence: 99%
“…j; k = 1; :::; n)(2) subject to a kj 2 [l kj ; u kj ]; 8j > k; a jk = 1 a kj ; 8j < k; a jj = 1 and similarly, S ui can be evaluated using the crisp mathematical programming model, j; k = 1; :::; n)…”
mentioning
confidence: 99%